Repeated-sprint ability - Part I: Factors contributing to fatigue - Girard, O.; Mendez-Villanueva, A.; Bishop, D. (Sports Medicine, 2011)
Short-duration sprints (<10 seconds), interspersed with brief recoveries (<60 seconds), are common during most team and racket sports. Therefore, the ability to recover and to reproduce performance in subsequent sprints is probably an important fitness requirement of athletes engaged in these disciplines, and has been termed repeated-sprint ability (RSA). This review (Part I) examines how fatigue manifests during repeated-sprint exercise (RSE), and discusses the potential underpinning muscular and neural mechanisms. A subsequent companion review to this article will explain a better understanding of the training interventions that could eventually improve RSA.